RIGEM: Membangun Karakter Anak Usia Dini melalui Lagu Anak di TK B - I Kadek Pande Ivnata Kusuma; Luh Made Dwi Wedayanthi (Lembaga Pengembangan Kinerja Dosen, 2025)
The RIGEM community service program was carried out with the aim of strengthening character education for early childhood through the use of children’s songs in TK B. The background of this activity stems from concerns about the increasing exposure of children to adult songs and content, which may influence their behavior and moral values. Children’s songs were chosen as the main medium because they have simple melodies, easy-to-remember lyrics, and contain positive values that can stimulate children's cognitive, affective, and social development. This study employs a descriptive qualitative approach using the CIPP evaluation model (Context, Input, Process, Product) to assess the effectiveness of the program. Data were collected through observations, interviews with teachers and parents, and documentation of activities. The results show that the children’s songs introduced particularly those containing messages about politeness, cooperation, and responsibility were effective in improving children's understanding of moral values and encouraging positive behavioral changes. Children became more accustomed to using polite expressions, showing empathy, and cooperating during classroom activities. Teachers and parents played an important role in reinforcing these habits both at school and at home. Overall, the RIGEM program proved to be an effective, enjoyable, contextual, and easily implemented effort to foster character development in early childhood education.